Superhydrophobicity in perfection: the outstanding properties of the lotus leaf - Ensikat, Hans J.; Ditsche-Kuru, Petra; Neinhuis, Christoph; Barthlott, Wilhelm (Beilstein Journal of Nanotechnology, 2011)
Lotus leaves have become an icon for superhydrophobicity and self-cleaning surfaces, and have led to the concept of the ‘Lotus effect’. Although many other plants have superhydrophobic surfaces with almost similar contact angles, the lotus shows better stability and perfection of its water repellency. Here, we compare the relevant properties such as the micro- and nano-structure, the chemical composition of the waxes and the mechanical properties of lotus with its competitors. It soon becomes obvious that the upper epidermis of the lotus leaf has developed some unrivaled optimizations. The extraordinary shape and the density of the papillae are the basis for the extremely reduced contact area between surface and water drops. The exceptional dense layer of very small epicuticular wax tubules is a result of their unique chemical composition. The mechanical robustness of the papillae and the wax tubules reduce damage and are the basis for the perfection and durability of the water repellency. A reason for the optimization, particularly of the upper side of the lotus leaf, can be deduced from the fact that the stomata are located in the upper epidermis. Here, the impact of rain and contamination is higher than on the lower epidermis. The lotus plant has successfully developed an excellent protection for this delicate epistomatic surface of its leaves.
Keywords: epicuticular wax; leaf surface; Lotus effect; papillae; water repellency